Extractive Spectrophotometric Determination of Gatifloxacin - Siva Prasad, K.V.; Prabhakar, G.; Murali Mohan Rao, S.V.; SANDHYA, M.; Jagganath, G. (Asian Journal of Chemistry, 2010)
Three simple and sensitive extractive spectrophotometric methods (A-C) have been developed for the determination of gatifloxacin (GTL) in bulk drug and pharmaceutical formulations. The developed methods involve formation of coloured chloroform extractable complexes of drug with wool-fast blue BL (WFB BL λmax 590 nm, Tropaeolineooo (TPooo, λmax 480 nm) and bromo phenol blue (BPB λmax 420 nm) in acidic medium. Beer's law is obeyed in the concentration ranges of 1-6 μg/mL, 1-6 μg/mL and 2-10 μg/mL respectively. The results of analysis for all three methods have been validated statistically and by recovery studies.